Interleukin-6 reduces NMDAR-mediated cytosolic Ca2+ overload and neuronal death via JAK/CaN signaling. Issue 3 (September 2015) - Ma, Song-Hua; Zhuang, Qian-Xing; Shen, Wei-Xing; Peng, Yu-Ping; Qiu, Yi-Hua
Graphical abstract